Semantic Web Rules International Symposium, RuleML 2010, Washington, DC, USA, October 21-23, 2010. Proceedings - Dean, Mike.; Hall, John.; Rotolo, Antonino; Tabet, Said.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the International RuleML Symposium on Rule Interchange and Applications, RuleML 2010, held in Washington, DC, USA, in October 2010 - collocated with the 13th International Business Rules Forum Conference 2010. The 14 revised full papers and 7 revised short papers presented together with the abstracts of 3 keynote lectures were carefully reviewed and selected from 42 submissions. The accepted papers address a wide range of rule topics, including traditional topics, such as rules and uncertainty, rule-based event processing and reaction rules, rules and inferencing, rule transformation and extraction, rules, semantic technology, and cross-industry standards, rules and norms, rule-based distributed/multi-agent systems, and miscellaneous rule topics.
Keynotes and Invited Demos -- Logical Spreadsheets -- NIEM Canonical XML Dictionaries and Rule Engine Systems -- Implementing SBVR with a Practitioner$1 (Bs Perspective -- Rules and Uncertainty -- A Practical Management of Fuzzy Truth-Degrees Using FLOPER -- A Rule-Based Implementation of Fuzzy Tableau Reasoning -- Rule-Based Event Processing and Reaction Rules -- Ensuring Compliance with Semantic Constraints in Process Adaptation with Rule-Based Event Processing -- Establishing a Procedure Model for Combining and Synergistically Aligning Business Rules and Processes within Ontologies -- Rules and Inferencing -- Rule-Based Contextual Reasoning in Ambient Intelligence -- Enhancing a Smart Space with Answer Set Programming -- Superiority Based Revision of Defeasible Theories -- On the Problem of Computing Ambiguity Propagation and Well-Founded Semantics in Defeasible Logic -- Rule Transformation and Extraction -- Generating SQL Queries from SBVR Rules -- Representing Financial Reports on the Semantic Web: -- Transformation of SBVR Compliant Business Rules to Executable FCL Rules -- Rules, Semantic Technology, and Cross-Industry Standards -- RuleML 1.0: The Overarching Specification of Web Rules -- Rules and Norms -- Defining Access Control Rules with Conditions -- Norm Compliance in Business Process Modeling -- Application of an Ontology-Based and Rule-Based Model to Selected Economic Crimes: Fraudulent Disbursement and Money Laundering -- Rule-Based Distributed/Multi-Agent Systems -- A Contract Agreement Policy-Based Workflow Methodology for Agents Interacting in the Semantic Web -- Photorealistic Semantic Web Service Groundings: Unifying RESTful and XML-RPC Groundings Using Rules, with an Application to Flickr -- Towards the Web of Models: A Rule-Driven RESTful Architecture for Distributed Systems -- Miscellaneous Rule Topics -- Visualizing Logical Dependencies in SWRL Rule Bases -- An XML Format for Association Rule Models Based on the GUHA Method -- Realizing Integrated Service Delivery through a Language for Collective Understanding of Business Rules -- Authoring Business Rules Grounded in OWL Ontologies.s
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information systems; Artificial intelligence; Computer Science; Software Engineering; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Information Systems Applications (incl.Internet).; Programming Techniques; Algorithm Analysis and Problem Complexity